Immediate effects of self-myofascial release on latent trigger point sensitivity: a randomized, placebo-controlled trial - Wilke, Jan; Vogt, Lutz; Banzer, Winfried (Biology of Sport, 2018)
Latent myofascial trigger points (MTrP) have been linked to several impairments of muscle function. The present study was conducted in order to examine whether a single bout of self-myofascial release using a foam roller is effective in reducing MTrP sensitivity. Fifty healthy, pain-free subjects (26.8±6 years, 21 men) with latent MTrP in the lateral gastrocnemius muscle were included in the randomized, controlled trial. One week after a familiarization session, they were randomly allocated to three groups: (1) static compression of the most sensitive MTrP using a foam roll, (2) slow dynamic foam rolling of the lateral calf and (3) placebo laser acupuncture of the most sensitive MTrP. Treatment duration in each group was 90 seconds. The pressure pain threshold (PPT) of the most sensitive MTrP was assessed using a handheld algometer prior to and after the intervention. A repeated measures analysis of variance (3x2) did not reveal significant between‑group interactions (p>.05) but showed a significant time effect (F=7.715, p .05), static compression of MTrP increased the PPT (2.6±0.8 to 3.0±1.1, d=.35; p<.05). Static self-myofascial release using a foam roller might represent an alternative to reduce pressure pain of latent MTrP. Additional research should aim to extend these findings to patients and athletes with myofascial pain syndromes.